2020
DOI: 10.1038/s41598-020-76729-4
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar molecular layer interneurons are dispensable for cued and contextual fear conditioning

Abstract: Purkinje cells are the only output cell of the cerebellar cortex. Their spatiotemporal activity is controlled by molecular layer interneurons (MLIs) through GABAA receptor-mediated inhibition. Recently, it has been reported that the cerebellar cortex is required for consolidation of conditioned fear responses during fear memory formation. Although the relevance of MLIs during fear memory formation is currently not known, it has been shown that synapses made between MLIs and Purkinje cells exhibit long term pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…These studies suggest that MLI-PC synapses play a role in auditory fear conditioning by regulating GABA release and endocannabinoid degradation ( Figure 2 ). A recent study, however, showed that mice with functional removal of GABA A -mediated signaling at MLI-PC synapses showed intact fear learning and memory (Marshall-Phelps et al, 2020 ), suggesting that the role of MLI-PC synapse in fear learning and memory remains to be further investigated.…”
Section: The Role Of the Cerebellum In Fear Learning And Memory In Ro...mentioning
confidence: 99%
“…These studies suggest that MLI-PC synapses play a role in auditory fear conditioning by regulating GABA release and endocannabinoid degradation ( Figure 2 ). A recent study, however, showed that mice with functional removal of GABA A -mediated signaling at MLI-PC synapses showed intact fear learning and memory (Marshall-Phelps et al, 2020 ), suggesting that the role of MLI-PC synapse in fear learning and memory remains to be further investigated.…”
Section: The Role Of the Cerebellum In Fear Learning And Memory In Ro...mentioning
confidence: 99%
“…Whilst Sacchetti et al (2004) mice deficient in parallel fibre-Purkinje cell synaptic potentiation had impaired fear response to conditioned stimuli (Sacchetti et al, 2004), Han et al (2021) further revealed that signal transducer and activator of transcription 3 (STAT3)-dependent molecular regulation of glutamatergic input to Purkinje cells is indispensable for proper expression of fear memory. In contrast, GABAergic input to Purkinje cells mediated via molecular layer interneurons is not required for both fear memory acquisition and recall (Marshall-Phelps et al, 2020).…”
Section: Intra Cerebellar Micro-circuit Mechanisms Supporting a Role ...mentioning
confidence: 89%
“…The proposed theory could be experimentally tested when genetic access to IN types are acquired. Disturbing IN1 alone or both INs would not disrupt LTD, as it keeps the CF and PF inputs intact 53 . Disturbing IN2 alone would disrupt LTD, as it destroys the disinhibitory pathway.…”
Section: Discussionmentioning
confidence: 99%